EL RÉGIMEN DE VACACIONES PARA EL TRABAJADOR, SEGÚN EL CÓDIGO DEL TRABAJO VULNERA EL DERECHO DE IGUALDAD ESTABLECIDO EN LA CONSTITUCIÓN DE LA REPÚBLICA - QUIZHPE VILLAVICENCIO, TATIANA ROSIBEL (2016)
The principle of equality is one of the rights that all Ecuadorians enjoy the same consisting of equal treatment for all people and condemns discrimination, we all have the same rights and guarantees under the law, no one can give a inegalitarian to a person because of religion, political affiliation, culture among other treatment. This research is walked to treat infringement of the right to equality, since in the labor code and the law on public service is making a distinction between the worker and the public servant, and if it is true that the worker serving physical or manual and intellectual public servant provides services both are workers and establishing different regimes vacation is being given unequal treatment and therefore is in breach of the right to equality. In our constitution of the Republic of Ecuador states that will be unconstitutional any rules that reduce the enjoyment and exercise of rights, this rule is being breached and that the labor code is set fortnight's holiday including non-working days for the year worker from working, this may have more one day after five consecutive years of work under the same employer, but this benefit may not exceed fifteen days, besides these extra days of holiday leave it for consideration by the employer as if it wants to give these extra days you give if it does not have the option of paying those days the worker. Instead of the Organic Law of Public Service regime for the server Vacation thirty days from the eleven months of work is established; this legal provision is decreasing exercise holidays apart worker who is taking some unequal treatment between the two types of workers. With this rock introduction is known that there is a serious problem in the Ecuadorian labor law, since there is inconsistency between the days of vacation for workers and public servants, causing this violation of their rights, and that is not complied with purpose of the holiday is rest and recovery of energy for the exercise of their duties; than before annotated I concluded establishing a proposed amendment to Art. 69 of the Labour Code guaranteeing the right to equality, through the implementation of a system of equal holidays between the worker and the public servant in order to comply faithfully the rights established and guaranteed by the constitution.